The Difference between Conventional and Mindfulness Education on Self-Efficacy of Pregnant Women at PMB Midwife “N”, SST Central Bogor District, Bogor City - permatasari, shintia; Nurul Husnul Lail; Risza Choirunissa (Rajaki of Tulip Medika Publisher, 2025)
Background: Anxiety in pregnancy is an indirect cause of death in mothers. In 2021 in West Java there were 36.2% of pregnant women who experienced anxiety in facing childbirth. Based on the results of data at PMB “N” in 2024 there were 90 pregnant women, the number of women giving birth was as many as people. The number of mothers who experienced prolonged labor and congestion during labor was 7 people (58%). Purpose: The purpose of this study is to determine the differences in self efficacy in third trimester pregnant women with the provision of conventional antenatal education and mindfulness. Methods: This study uses a quasi experimental design approach. Sampling by quota sampling to get 20 third trimester respondents who were divided equally into 2 groups, namely experimental and control groups. The intervention was given for 7 days. The research instruments used in this study included the Child-birth Self-Efficacy (CBSE- 32) quiz in the Indonesian version. Data were analyzed using the Mann-Whitney Test to determine differences in influence between groups. Result: The results showed that there was a significant difference in the increase in self-efficacy after being given mindfulness education with a total of 8 (80%) sure and p-value 0.001. While antenatal education with as many as 6 (60%) sure and p-value 0.044 at PMB Bd “N” SST Bogor City in 2024. The Mindfulness group showed more significant changes than the conventional group after the intervention. This indicates that the mindfulness intervention provided is more effective in increasing self-efficacy. Conclusion: This study provides evidence that mindfulness practice effectively increases self-efficacy in third trimester pregnant women. Thus, mindfulness is expected to be part of antenatal education for pregnant women in self-empowerment to increase self-efficacy before labor and improve the quality of medical services.